The Effect of Type 2 Diabetes Mellitus and Obesity on FIB-4 Index Screening for Early Hepatic Fibrosis in Nonalcoholic Fatty Liver Disease - ZHUO Lili, QU Huanjia, ZHANG Qiuling (Zhongguo quanke yixue, 2025)
Background With the prevalence of obesity, the incidence of non-alcoholic fatty liver disease (NAFLD) is increasing, the risk of liver fibrosis and liver cancer is also increasing. Screening for early fibrosis is of great significance. International guidelines recommend fibrosis-4 (FIB-4) index as an indicator for screening hepatic fibrosis. However, it is unclear whether FIB-4 index screening is affected by type 2 diabetes and BMI in screening for early fibrosis. Objective To evaluate whether the effectiveness of FIB-4 index in primary care screening is affected by type 2 diabetes and BMI. Methods A total of 110 patients diagnosed with NAFLD by liver biopsy in the Affiliated Hospital of Hangzhou Normal University from 2013 to 2023 were selected as the study objects. They were divided into type 2 diabete (T2DM) group and non-T2DM group according to T2DM. According to BMI, they were divided into normal weight group, overweight group and obesity group. According to the liver biopsy results, they were divided into F0-F1 group and F2-F4 group. FIB-4 index was calculated and the differences among each group were compared. Spearson correlation was used to analyze the correlation between FIB-4 index and various indexes. The accuracy of FIB-4 index was evaluated via receiver operating characteristics (ROC) curves. The area under ROC curve (AUC) was calculated and Delong test was used to compare AUC differences between groups. Results The comparison results of FIB-4 index showed that the T2DM group was higher than non-T2DM group, and F0-F1 group was lower than F2-F4 group with statistical significance (P<0.05). There was no significant difference in FIB-4 index among normal weight group, overweight group and obesity group (P>0.05). Correlation analysis showed that FIB-4 index was positively correlated with age, aspartate aminotransferase, fasting glucose and fibrosis (P<0.05), and negatively correlated with platelet count (P<0.05). The AUC of FIB-4 index in the diagnosis of NAFLD was 0.77 (95%CI=0.68-0.86, P<0.001) and the AUC of FIB-4 index in the diagnosis of NAFLD with T2DM was 0.85 (95%CI=0.72-0.98, P<0.001). The AUC of FIB-4 index in the diagnosis of NAFLD without T2DM was 0.71 (95%CI=0.58-0.84, P=0.006). Delong test results showed that there was no significant difference in AUC between the T2DM group and the non-T2DM group (Z=1.509, P=0.131). The AUC of FIB-4 index in the diagnosis of NAFLD was 0.91 (95%CI=0.76-1.00, P=0.029) in the normal group, 0.65 (95%CI=0.46-0.83, P=0.125) in the overweight group, and 0.82 (95%CI=0.70-0.94, P<0.001) in the obese group. The AUC of the normal group was higher than that of the overweight group, and the difference was statistically significane (Z=2.037, P=0.042). There was no significant difference in AUC between the obese group and the normal group or the overweight group (Z=0.876, P=0.381; Z=1.452, P=0.146) . Conclusion FIB-4 is not affected by T2DM in the assessment of early fibrosis in NAFLD patients, but has a certain relationship with BMI.